(untitled) (Homoeopathy for All, 2026)
In daily practice, one repeatedly meets patients who seem to react out of all proportion to the apparent cause. One patient begins to sneeze every spring as if the season itself had become an adversary. Another develops burning eyes and fluent coryza from flowers, dust, or slight atmospheric change. A third breaks into urticaria after a particular food, while yet another passes from recurrent nasal irritation into tightness of chest and asthmatic suffering. Modern medicine commonly gathers many such states under the word allergy. Yet the attentive physician soon realizes that the deeper question is not merely the external cause, but the peculiar manner in which the individual organism receives and answers it.